Frequency Optimization Objective during System Prototyping on Multi-FPGA Platform. (17th December 2013) - Turki, Mariem; Marrakchi, Zied; Mehrez, Habib; Abid, Mohamed
Abstract : Multi-FPGA hardware prototyping is becoming increasingly important in the system on chip design cycle. However, after partitioning the design on the multi-FPGA platform, the number of inter-FPGA signals is greater than the number of physical connections available on the prototyping board. Therefore, these signals should be time-multiplexed which lowers the system frequency. The way in which the design is partitioned affects the number of inter-FPGA signals. In this work, we propose a set of constraints to be taken into account during the partitioning task. Then, the resulting inter-FPGA signals are routed with an iterative routing algorithm in order to obtain the best multiplexing ratio. Indeed, signals are grouped and then routed using the intra-FPGA routing algorithm: Pathfinder. This algorithm is adapted to deal with the inter-FPGA routing problem. Many scenarios are proposed to obtain the most optimized results in terms of prototyping system frequency. Using this technique, the system frequency is improved by an average of 12.8% compared to constructive routing algorithm.